Integrative literature review step-by-step & convergences with other methods of review - Elizabeth Teixeira, Horácio Pires Medeiros, Marcia Helena Machado Nascimento, Bruna Alessandra Costa e Silva, Camila Rodrigues (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v2i5.1457